Gamification: The using of user discussion groups in the software development in e-banking - Rodrigues, L.; Costa, C.; Oliveira, A. (ISDOC 2014: Proceedings of the International Conference on Information Systems and Design of Communication, 2014)
The development of the new software game gave emphasis and importance to the role played by the user discussion group during the development phase; they were sometimes called upon to participate in testing and they contributed to changes that improved the overall software’s. Some more concrete methods include discussion groups to stimulate the emergence of new ideas and evaluate the gamification concepts. According to this approach, the web designers of two gamification software projects in e-banking using Mutual Funds and Warrants were encouraged to build the first playable version of the gamified business software. After a live introduction to a group of users, it was requested their opinion in an open questionnaire with six questions, permitting them to identify without restrictions the needs, modifications and opinions. The method has identified a wide range of games characteristics and web design changes, as was expected by both business and customers. In conclusion, the use of the discussion group and open questionnaires were effective methods for the project team, to check preview the perceptions and customer acceptance in adopting the software gamified. In this study, we identified the users' perceptions, resumed in a diagram “the most relevant factors in an e-business game”. Our practical contribution is for the web designers and project managers who with this methodology, may check if their software will have good adoption.